Changes in the summit flora of a Mediterranean mountain (Sierra Nevada, Spain) as a possible effect of climate change - Fernández Calzado, Maria Rosa; Molero Mesa, Joaquin (Lazaroa, 2013)
The evidences on climate change-induced impacts on alpine plant communities is growing and some of them warn us about the expected changes in vegetation of the generally fragmented Mediterranean high mountain areas in a projected warmer and drier future. Short-term (2001-2008) changes in vascular plants species number, cover and subplot-frequency were studied on four summits in the Sierra Nevada (Spain). The resurvey revealed a decrease in species richness on each summit, which is confirmed by small-scale changes in species frequency within the same summits. These changes involve local losses of several high-elevation endemic species as well as the new appearance of predominantly more widespread species. Some of the latter species were also observed to expand elsewhere in the Sierra Nevada. On a small scale, cover of several endemic species decreased and cover of some species that occur on a wider vertical range increased. Although the observed changes are statistically only marginally or not significant, they are largely consistent with pan-European studies suggesting a stagnant or declining species richness on summits of the Mediterranean biome and a ‘thermophilisation’ of the species composition in high mountain plant communities over the past years. Even though we cannot rule out other non-climatic factors, our results give rise to concern about the situation of the mainly endemic high-altitude flora of the Sierra Nevada and give an incentive to intensify monitoring efforts.